The early marriage of the Tolaki Konawe community in the perspective of critical Islamic law - Kamaruddin Kamaruddin (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2022)
The Konawe people have a unique tradition of early marriage. Research from a critical Islamic perspective has yet to be widely studied in this tradition. This study investigated the initial legitimacy process as an ethnic tradition in early marriage. A legal ethnographic case study design was used in this study. Thirteen individuals participated in the study, including four community leaders, three indigenous peoples, two academics, and four parents of early marriage doers. In-depth interviews and observation were used to collect the data. Reduction, presentation, and interpretation are all used in data analysis methods. The study revealed three key findings: First, the chieftain decides on early marriage in the Tolakiness community. Second, decisions and agreements must be followed and upheld by everyone in the community. Thirdly, different legal systems—such as Islamic, Indonesian, or Western civil law—impact these judgments and agreements, which alters the relationship between law and freedom. This article argued that the Tolakian community needs to undergo cultural reconstruction to accommodate women's rights and freedoms and avoid coercive judgments from tribal chiefs.